STRATEGI PEMBELAJARAN AGAMA ISLAM BAGI SISWA AUTIS DI SLB NEGERI METRO - Tisnawati, Nina; Islahudin, Ahmad Noor; Garianto, Garianto (Lembaga Penelitian UM Metro, 2024)
This research discusses Islamic religious learning strategies for autistic class students at the Metro State Special School. This research focuses on how appropriate learning strategies can be delivered to autistic students, who have different ways of learning from children in general. This requires teachers to be given appropriate direction and strategies in delivering Islamic religious lessons, which is currently only done once a week by their respective homeroom teachers. Application of learning is an activity carried out by SLB teachers using appropriate methods and utilizing various media for students, with the aim of achieving learning objectives. Islamic religious lessons for autistic students require a special approach so that they can be well received. Emotional approach and demonstration method are some of the effective strategies. Apart from that, religious activities are held on religious holidays, such as daily prayer reading competitions and short letters between students. The aim of this research is to find out how effective Islamic learning strategies are for autistic students, so that the messages conveyed by teachers can be well received by them.